Spontaneous tumour lysis syndrome at presentation in an infant with hepatoblastoma: A rare occurrence - Srinivas Srinidhi Vadlapudi; Anshu Srivastava; Nilay Nishith; Moinak Sen Sarma; Ujjal Poddar; Rakesh Pandey (Elsevier, 2021)
A ten-month-old infant presented with large hepatomegaly, hypertension and clinical tumour lysis syndrome (TLS). Computerized tomography of the abdomen and chest was suggestive of hepatoblastoma (HB) with lung metastasis. Serum alpha-fetoprotein was elevated and liver biopsy showed epithelial, fetal type of HB. TLS resolved with medical therapy following which chemotherapy was initiated. However, the child succumbed to febrile neutropenia and sepsis. TLS is uncommon in solid tumours and described in bulky, metastatic and highly chemo-sensitive tumours especially following chemotherapy or during surgery. However, our child had TLS at presentation without any prior therapy. Hence, children with hepatoblastoma especially those with risk factors need to be screened for TLS. Both TLS and hypertension need timely intervention to prevent further complications.